Literatur nach der Digitalisierung - Kreuzmair, Elias; Schumacher, Eckhard (Gegenwartsliteratur, 2021)
Digital media are transforming narratives and literary texts. They are also changing how we think about the present. It is against this backdrop that this volume inquires into the status of contemporary literature after digitalization: What role do new concepts of time play in writing? What forms of temporal reflection have shaped the novels of the last fifteen years? Which new modes of writing are being developed in digital media?